Wavelength‐Tunable, Long Lifetime, and Biocompatible Luminescent Nanoparticles Based on a Vitamin E‐Derived Material for Inflammation and Tumor Imaging. Issue 25 (24th May 2021) - Yan, Xinhao; Lin, Wenjie; Liu, Huan; Pu, Wendan; Li, Junhong; Wu, Peng; Ding, Jun; Luo, Gaoxing; Zhang, Jianxiang
Abstract: Luminescence imaging is one of the most effective noninvasive strategies for detection and stratification of inflammation and oxidative stress that are closely related to the pathogenesis of numerous acute and chronic diseases. Herein biocompatible nanoparticles based on a peroxalate ester derived from vitamin E (defined as OVE) are developed. In combination with different fluorophores, OVE can generate luminescence systems with emission wavelengths varying from blue to the near‐infrared light in its native and nanoparticle forms, in the presence of hydrogen peroxide (H2 O2 ). The OVE‐based nanoprobes exhibit high luminescence signals with extremely long lifetime, upon triggering by inflammatory conditions with abnormally elevated H2 O2 . Activated neutrophils and macrophages can be illuminated by this type of luminescent nanoprobes, with luminescence intensities positively correlated with inflammatory cell counts. In mouse models of peritonitis, alcoholic liver injury, drug‐induced acute liver injury, and acute lung injury, the developed luminescence nanoprobes enable precision imaging of inflammation and disease progression. Moreover, tumors expressing a high level of H2 O2 can be shined. Importantly, the OVE‐based nanoplatform shows excellent in vitro and in vivo biocompatibility. Abstract : Wavelength‐tunable, long lifetime, and biocompatible luminescent nanoparticles based on a vitamin E‐derived hydrogen peroxide‐responsive material and extensively available fluorescent molecules are engineered by a facile strategy. Thus developed self‐illuminating nanoprobes with emission wavelengths varying from blue to near‐infrared light enable effective luminescence imaging of multiple diseases related to inflammation/oxidative stress and tumors with high reactive oxygen species.